Impact of Pesticide Quality Control Programme in Southern Punjab, Pakistan: Pesticide Quality Control Programme - Mubeen, Khuram; Sarwar, Naeem; Akhtar, Muhammad Waseem; Akhtar, Muhammad Naeem; Rahi, Ashfaq Ahmed; Munir, Shahid; Rafique, Hafiz Muhammad (Biological Sciences - PJSIR, 2018)